Specific defect in N-acetylglucosamine incorporation in the biosynthesis of the glycosylphosphatidylinositol anchor in cloned cell lines from patients with paroxysmal nocturnal hemoglobinuria - Hillmen, P; Bessler, M; Mason, P J; Watkins, W M; Luzzatto, L (Proceedings of the National Academy of Sciences - PNAS, 1993)
Paroxysmal nocturnal hemoglobinuria (PNH) is a clonal disorder arising in a multipotent hemopoietic stem cell. PNH manifests clinically with intravascular hemolysis resulting from an increased sensitivity of the red cells belonging to the PNH clone to complement-mediated lysis. Numerous studies have shown that surface proteins anchored to the membrane via a glycosylphosphatidylinositol (GPI) anchor (including proteins protecting the cell from complement) are deficient on the cells of the PNH clone, leading to the notion that GPI-anchor biosynthesis may be abnormal in these cells. To investigate the biochemical defect underlying PNH we have used lymphoblastoid cell lines (LCLs) with the PNH phenotype obtained by Epstein-Barr virus immortalization of lymphocytes from nine patients with PNH. By labeling cells with myo-[3H]inositol we have found that PNH LCLs produce phosphatidylinositol normally. By contrast, PNH LCLs fail to incorporate [3H]mannose into GPI anchor precursors. When cell-free extracts of PNH LCLs and normal LCLs obtained from the same patients (and expected therefore to be isogeneic except for the PNH mutation) were incubated with uridine diphospho-N-acetyl[3H]glucosamine (UDP-[3H]GlcNAc), we observed complete failure or marked reduction in the production of N-acetylglucosaminyl(alpha-1,6)phosphatidylinositol and glucosaminyl(alpha-1,6)phosphatidylinositol by the PNH LCLs in all cases. These findings pinpoint the block in PNH at an early stage in the biosynthesis of the GPI anchor, suggesting that the defective enzyme is UDP-GlcNAc:phosphatidylinositol-alpha-1,6-N- acetylglucosaminyltransferase. The existence of PNH type III cells and type II cells is probably explained by the transferase deficiency being total or partial, respectively.